(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the improvement of methodological approaches for developing trainees’ professional readiness for inclusive education in the process of professional development. The relevance of the study is determined by the growing need to prepare teachers who are able to work effectively with learners with diverse educational needs, create an inclusive classroom environment, and apply differentiated pedagogical strategies. The article analyzes the content of professional readiness as an integrated quality that includes theoretical knowledge, practical skills, positive attitudes, communicative competence, and reflective ability. Special attention is given to the role of professional development courses in updating teachers’ pedagogical thinking, strengthening their competence in inclusive education, and helping them master modern instructional technologies. The study emphasizes that the effectiveness of inclusive education depends not only on legal and institutional support, but also on the methodological quality of teacher training. The proposed approach is aimed at improving the content, forms, methods, and assessment criteria of professional development programs.